S88 The viral mimic polyinosinic: polycytidylic acid (Poly I:C) induces TRPA1 channel hyper-responsiveness in an adult human stem cell-derived sensory neuronal model. (12th November 2015) - Clarke, R; Monaghan, K; About, I; El Karim, I; McGeown, JG; Cosby, SL; Curtis, TM; Lundy, FT; McGarvey, L
Abstract : Background: Changes in airway neuronal activity are likely to underpin the heightened irritant responses such as excessive cough and wheeze which accompany respiratory virus induced exacerbations of airways disease. The mechanisms responsible are unknown but we hypothesised that neurons express pathogen recognition receptors such as toll-like receptors (TLR) through which viruses may alter neural function. Investigating this is hampered by the lack of suitable human tissues with both nerve endings and cell bodies present. We have refined an adult human neural crest stem cell-derived sensory neuronal model to overcome this obstacle. Methods: Human dental pulp stem cells (hDPSCs) were differentiated towards a neuronal phenotype, termed peripheral neuronal equivalents (PNEs). Using molecular and immunofluorescent techniques, together with whole cell patch clamp electrophysiology, we investigated the expression and function of TLRs and the transient receptor potential (TRP) channels TRPV1 and TRPA1 on PNEs. We then assessed the effects of exposure to a viral mimic, the synthetic TLR3 agonist (polyI:C), on cytokine release and changes in the PNE responsiveness to the TRPA1 channel agonist cinnamaldehyde (100 µM). Results: hDPSCs undergo a fibroblastic to neuronal phenotypic switch to PNEs which express the sensory neuronal proteins SP and CGRP. Using qPCR we confirm that PNEs express TLR3, TLR4 and TLR7 mRNA and functional expression of TRPA1 and TRPV1 channels. PNEs pre-treated with PolyI:C (2 µg/ml) for 20 mins generated significantly larger inward (-10.8773 pA/pF; p < 0.01) and outward (10.0507 pA/pF; p < 0.01) currents in response to cinnamaldehyde (100 µM) compared to untreated PNEs (-2.347 pA/pF and 2.872 pA/pF respectively). The electrophysiological events elicited by PolyI:C occurred rapidly, were not sustained and appeared independent of alteration in TRP channel gene expression. PNEs incubated with PolyI:C for 24 h released significantly greater IL6 (246.504 pg/ml; p < 0.01) and IL8 (2140.83 pg/ml; p < 0.001) levels compared to untreated PNEs. Conclusion: Using a novel human in vitro sensory neuronal model we observed that Poly I:C evoked sensory neuronal hyper-responsiveness with an accompanying pro-inflammatory response. Respiratory viruses may induce similar effects on sensory neurons during exacerbations of airways disease.